He crashed me so I crashed him back : the true story of the year the King, Jaws, Earnhardt, and the rest of NASCAR's feudin', fightin', good ol' boys put stock car racing on the map - Bechtel, Mark. (New York : Little, Brown and Co., 2010)
The story of how Bobby Allison, Donnie Allison, Cale Yarborough, Richard Petty, Dale Earnhardt, Darrell Waltrip, A.J. Foyt, and Kyle Petty came together in an unforgettable season that featured the first nationally televised NASCAR races.
Something borrowed, something blue -- Birthplace of speed -- The good ol' boys -- The prince -- The man in the white hat -- On the air -- So fair and foul a day -- The fight - - Round two -- Round three -- Wild and young, crazy and dumb -- Diamonds as big as horse turds -- Pearson's kerfuffle -- Old Chow Mein -- Bring on the dancing bears - - Gassed -- Rising again -- The Gatorade Kid -- The beginning of the trouble -- Pretty good Americans -- The shootout.
Includes bibliographical references and index.
Keywords: NASCAR (Association) -- History; Stock car racing -- United States -- History; Stock car drivers -- United States